Revisiting the DeLone and McLean Model: System Quality, Information Quality, and Service Quality as Determinants of Driver Satisfaction in Ride-Hailing Platforms - Kulla, Emti; Ardianto, Yusaq Tomo; Yuniawan, Dani (Journal of Regional Economics Indonesia, 2025)
This study investigates the effects of system quality, information quality, and service quality on driver satisfaction in a ride-hailing platform context. The research focuses on drivers using the Maxim application in Mimika Regency, Central Papua, Indonesia. A quantitative explanatory approach was employed using survey data collected from 114 drivers. Data were analyzed using multiple regression and path analysis to examine both partial and simultaneous effects of the independent variables on driver satisfaction. The results indicate that information quality has a significant positive effect on driver satisfaction, while system quality and service quality do not show a significant direct influence. However, jointly, the three variables significantly explain variations in driver satisfaction, accounting for 63.1% of the total variance. These findings suggest that accurate, complete, and timely information plays a critical role in shaping driver satisfaction, particularly in regions with geographical and infrastructural constraints. This study contributes to the literature on information systems success by providing empirical evidence from an emerging and peripheral regional context.